2012
DOI: 10.1016/j.ijgo.2011.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of “push” and “pull” methods for impacted fetal head extraction during cesarean delivery

Abstract: Although the pull method may lead to some neonatal complications, it is associated with lower maternal morbidity than the push method when used for impacted fetal head extraction during cesarean delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 11 publications
2
56
1
Order By: Relevance
“…The risk of lateral or downward extension of the uterine incision was approximately 8 times higher with the push method (OR 7.8; 95% CI, 5.01-12.25) than with the pull method [19,25,42,43] and was consistent in all studies, and heterogeneity testing did not show any significant variation between the studies(I 2 =17.1%). Some authors [2,40] investigated lateral and downward incisions separately and found that lateral extensions were more common than vaginal extensions if the push method was used.…”
Section: Incision Extensionmentioning
confidence: 97%
See 4 more Smart Citations
“…The risk of lateral or downward extension of the uterine incision was approximately 8 times higher with the push method (OR 7.8; 95% CI, 5.01-12.25) than with the pull method [19,25,42,43] and was consistent in all studies, and heterogeneity testing did not show any significant variation between the studies(I 2 =17.1%). Some authors [2,40] investigated lateral and downward incisions separately and found that lateral extensions were more common than vaginal extensions if the push method was used.…”
Section: Incision Extensionmentioning
confidence: 97%
“…In this method, after opening the uterus, the surgeon introduces a hand through the uterine incision towards the upper segment, grasps both feet, and gently pulls the fetus up to extract it through the uterine incision [25].…”
Section: 'Reverse Breech Extraction' or The 'Pull Technique'mentioning
confidence: 99%
See 3 more Smart Citations